THE MEANING OF PRACIMAYASA BUILDINGS PURA MANGKUNEGARAN SURAKARTA - Sunarmi Sunarmi; Bani Sudardi; Pande Made Sukerta; Titis Srimuda Pitana (Proceeding of International Conference on Art, Language, and Culture, 2017)
The Meaning of Pracimayasa Building Pura Mangkunegaran Surakarta is a study of cultural studies. The problem of research, how the significance signs of Pracimayasa building Pura Mangkunegaran Surakarta. Globalization moves on the spirit and morality in favor of the interests of material activity. Pracimayasa building as a cultural heritage building used as a commodity in the global era. Research using critical approach with theory of deconstruction supported the theory of visual communication semiotics. The study is expected to give an opportunity to develop the creativity of interpreting the text, the interior of the cultural heritage building. Data collection with observation techniques, interviews, document studies and literature.The results showed that Pracimayasa building is the residence of the palace family especially for keputren. The reality of the building's private sign Pracimayasa seen from the location of buildings that are protected from other buildings and adjacent to the core building. The reality of keputren can be seen from the type of space and visual form Pracimayasa building. As a family residence, Pracimayasa buildings included in territorial areas that are not easily accessible physically and etiquette, not all ethical people enter. Therefore Pracimayasa building as a family residence is a symbol of ethics and manners within the life of Java.